A política de educação inclusiva nas escolas municipais de Toledo – Paraná no período de 2008 a 2012: um estudo da implementação das salas de recursos multifuncionais - Silveira, Bruna Nathaly (2015)
The theme of Inclusive Education in Brazil has been the subject of numerous reflections in various fields of knowledge. In Brazil, the law called Special Education Policy from the perspective of Inclusive Education was approved by the federal government in 2008. Given this process, this work has as object of research Special Education Policy from the perspective of Inclusive Education in the city of Toledo, Paraná state. The central objective of the research was to analyze the implementation of the multi-functional features defined in Decree-Law 03/2008 of 7 January 2008, which established the Special Education Policy in the context of inclusive education in public schools in Toledo / PR, from 2008 to 2012. To meet this goal, the methodological choices to be characterized as a survey of exploratory and field, qualitative and quantitative. On the choice of the subjects were selected two municipal schools according to the following criteria: presence of multifunctional resource room - the main instrument of the specialized education of Inclusive perspective -, region and socioeconomic characteristics of the region - to achieve the various municipal settings. Considering the central objective of the research and the settings described above, the first chapter aims to provide answers to the first specific objective of this research, which was to present the influence of international organizations in the construction of special education policies and the perspective of Inclusive Education in Brazil. This analysis was based on the study of secondary sources. The second chapter aims to provide answers to the second proposed specific objective, which was analytically discuss the role / function of the Brazilian state in the face of special education policies in Brazil, based on a literature review. In response to the third specific objective, which was analytically describe the process of construction of the municipal education network in Toledo / PR and its characterization from the years 2008 to 2012, and the fourth specific goal was, and identify educational instruments and existing physical infrastructure in public schools in Toledo described in Decree-Law 03/2008 of 7 January 2008 establishing the Special Education Policy in the context of inclusive education, the third chapter presented an analysis of the pedagogical political projects of the selected schools and analysis of participant observation in multi-functional features of these schools. Analysis of these instruments considered the forecast of Inclusive Education Policy and the determinations of the CNE / CEB number 13/2009 establishing the specialized educational services, pointed the elements that identify the perspective of Inclusive Education in Schools. From the analyzes, it was found that the two schools analyzed subjects, the prospect of Inclusive Education was identified in school documents - teaching political projects, and school reality - regarding the implementation of multi-functional features. It was found that, the gateway to the regular education, which is the living multifunction capabilities, is in operation, but the network to support this call not to the satisfaction occurs. It was also observed that there is correspondence between the international, national and school documents for guidance from the perspective of Inclusive Education, and although these documents describe the objective of political access, retention and quality of care for pupils with special educational needs, the foundation primeval these documents, which is the capitalist mode of production, access privileges, considering that this is 10 what allows the universalization of education and the entry of the poorest countries in the globalization game. Thus, both formally as real plan of the policy match. The reality / real plan materializes the law / formal plan as also highlights the access of students with special educational needs in mainstream education through multi-functional features but does not guarantee the permanence and quality of care through the support network these services.